Nano-structured Electrode Materials with Reduced Amount of Platinum Aimed for Hydro gen Evolution. Part II: Effect of MWCNTs modification - Ana Tomova; null, null; Perica Paunovic (INTERNATIONAL SCIENTIFIC JOURNAL "INDUSTRY 4.0", 2023)
Direct Metal Laser Sintering (DMLS) is a revolutionary technology that allows a production of fully functional metal parts directly from a 3D CAD data, eliminating the investment to production tools and technologies which brings considerable cost and time savings. Metal parts made by DMLS technology are fully comparable with casted or machined parts. A range of application of DMLS technologies is very wide – from prototypes, through short-run production to final products. Advantages of DMLS technology are arising along with com plexity of parts – more complex geometry of parts (in terms of shape and occurrence of the detail) make DMLS technology even more eco nomically effective.
Keywords: HYDROGEN ECONOMY, CATALYST SUPPORT, MWCNTs MODIFICATION, COBALT, PLATINUM